Arab aid : past, present and future : speeches... (The Fund ViennaAT, 2003)
Offers an insight into the world of Arab development finance, from its genesis, through years of consolidation and refinement, to its current role and future prospects. Looks also at Arab aid in Latin America and the Caribbean.
Keywords: DEVELOPMENT AID